New Tools for Epilepsy Therapy - Falcicchia, Chiara; Simonato, Michele; Verlengia, Gianluca (Frontiers in Cellular Neuroscience, 2018)
One third of the epilepsies are refractory to conventional antiepileptic drugs and, therefore, identification of new therapies is highly needed. Here, we briefly describe two approaches, direct cell grafting and gene therapy, that may represent alternatives to conventional drugs for the treatment of focal epilepsies. In addition, we discuss more in detail some new tools, cell based-biodelivery systems (ECB devices) and new generation gene therapy vectors, which may help in the progress toward clinical translation. The field is advancing rapidly, and there is optimism that cell and/or gene therapy strategies will soon be ready for testing in drug-resistant epileptic patients.